Model Pembelajaran Berbasis Masalah untuk Meningkatkan Hasil Belajar IPA Siswa Kelas IV SD Islam Raden Patah Surabaya - Fahmi, Ahmad Izzul (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2023)
This research aims to improve the learning achievement of fourth grade students at Raden Patah Islamic Elementary School, Surabaya in Natural and Social Sciences (IPAS) subjects through the application of a problem-based learning model (Problem Based Learning). The method used was classroom action research. The subjects of this research were class IV students, with data collection techniques through observation, tests and documentation. Data analysis was carried out qualitatively using the Miles and Huberman (1994) technique, which includes data reduction, data display, and drawing conclusions. The research results show that the application of the problem-based learning model succeeded in improving student learning outcomes significantly. At the Pre-Cycle stage, the average student score was 60, indicating low learning achievement. After implementing the problem-based learning model in Cycle I, the average student score increased from 69.17 to 75.83. Even though there has been an increase, these results have not yet reached the Minimum Completion Criteria (KKM). In Cycle II, after reflection and improvement, there was a more significant improvement. The average student score at the first meeting of Cycle II reached 83.75 and increased to 92.08 at the second meeting. The conclusion of this research is that the problem-based learning model is effective in improving the learning achievement of class IV students in science. This model is able to make learning more interesting and interactive, and avoids passive student involvement, so it can be applied as a better alternative to the conventional lecture model.